1990
DOI: 10.1038/hdy.1990.65
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic expression of modified chromosome constitution and structure in × Triticosecale Wittmack

Abstract: The chromosome constitution and the meiotic behaviour of plants in the F3, F4 and F6 progenies of one cross between 6x-triticale (female) and Triticum aestivum (male) were analysed. C-banding of meiosis proved to be a good method to score the individual levels of pairing, to verify the chromosome constitution, and to detect structural variations. Amongst the plants examined, the chromosome constitution varied in the third genome (0-7" D and 0-6" R), and all plants had the whole A and B genomes in common. Rye c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…These results and those obtained in the present work showed similar behaviour in triticale x trigopiro hybrids, since all became stabilized with 2n = 42 and retained the rye R genome. The same tendency was observed in different hybrids involving wheat ( Bernardo et al , 1988 , Soler et al , 1990 ). Bernardo et al (1988) studied rye chromosome behaviour in the progeny from AABBR hybrids, and proposed that there was total elimination of rye chromosomes when individually present but retention when the complete genome was present.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results and those obtained in the present work showed similar behaviour in triticale x trigopiro hybrids, since all became stabilized with 2n = 42 and retained the rye R genome. The same tendency was observed in different hybrids involving wheat ( Bernardo et al , 1988 , Soler et al , 1990 ). Bernardo et al (1988) studied rye chromosome behaviour in the progeny from AABBR hybrids, and proposed that there was total elimination of rye chromosomes when individually present but retention when the complete genome was present.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have shown that rapid genome changes occur following F 1 or allopolyploid formation: 1) the non-random elimination of coding and non-coding DNA sequences; 2) epigenetic changes, such as DNA methylation of coding and non-coding DNA, leading, among other things, to gene silencing; 3) the activation of genes and retro-elements, which, in turn, alters the expression of adjacent genes ( Feldman and Levy, 2005 ); and 4) chromosome reorganization, with the gain or loss of chromosomes or whole genomes ( Bernardo et al , 1988 ; Soler et al , 1990 ; Soltis and Soltis, 2000 ; Ferrari et al , 2005 ). An example of a particular case of the harmonic coexistence of several genomes achieved by chromosomal rearrangement and gain or loss of chromosomes or even completed genomes, was observed in the tricepiro Don René INTA ( Ferrari et al , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a telomeric band on rye chromosome arms does not always indicate a translocation. Rye chromosomes show a tendency for band deletion both in rye (Weimarck 1975, Pilch 1981a,b, Lukaszewski and Kopecky, 2010 and in triticale (Lukaszewski and Apolinarska 1981, Ziauddin and Kasha 1982, Soler et al 1990). The observed structural aberrations in distribution of heterochromatin in chromosomes of the analysed plants, as compared to the Giemsa C-banded karyotype of rye (Gill and Kimber 1974) require further research.…”
Section: Discussionmentioning
confidence: 99%
“…FISH with AhTR2-1 and Arabidopsis-type telomeric PNA-FISH as probes both revealed the absence of heterochromatic blocks to one or both homologues of chromosomes 4. Soler et al (1990) reported that subtelomeric heterochromatin is a region of instability, where amplification, deletion and even complete loss of heterochromatin could occur. The polymorphisms in A. hortensis do not seem to affect chromosome pairing and segregation in meiosis, or the production of fertile gametes (unpublished and Mlinarec et al 2006).…”
Section: Heterochromatin Polymorphisms Between Speciesmentioning
confidence: 98%